Doing Business in Kazakhstan 2019 - World Bank Group (World Bank, Washington, DC, 2019)
Doing Business in Kazakhstan 2019 focuses on business regulations and their enforcement across four Doing Business areas. It goes beyond Almaty City to benchmark the cities of Nur-Sultan and Shymkent, as well as thirteen other Kazakhstani regions across four regulatory areas. This report contains data current as of December 15, 2018 and includes comparisons with other economies based on data from Doing Business 2019: Training for Reform. Doing Business measures aspects of regulation that enable or hinder entrepreneurs in starting, operating or expanding a business—and provides recommendations and good practices for improving the business environment.